2021
DOI: 10.33774/chemrxiv-2021-46790-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amphotericin B Assembles into Seven-Molecule Ion Channels in Membrane Domain

Abstract: Amphotericin B, a long-used antifungal drug, forms fungicidal ion-permeable channels across cell membranes. Using solid-state nuclear magnetic resonance spectroscopy and molecular dynamics simulations, we experimentally elucidated the three-dimensional structure of the molecular assemblies formed by this drug in membranes in the presence of the fungal sterol, ergosterol. A stable assembly of seven drug molecules was observed to form an ion conductive channel. The structure somewhat resembled the upper half of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Most recent evidence in favor of the barrel-stave model was provided by the Murata group, who employed a set of 19 F-and 13 C-labeled AmB derivatives to structurally characterize the AmB-ergosterol channel assembly by solidstate NMR and molecular dynamics calculations. [30,31,[39][40][41] Analysis of the assembly of 14-F-AmB using the Centerband-Only Detection of Exchange (CODEX) NMR method to study slow molecular dynamics revealed that an average of seven AmB molecules were present in each assembly. Structural information was gained from crystallographic data and Rotational Echo Double Resonance (REDOR) NMR experiments designed to measure the distance between two selected labeled heteronuclei.…”
Section: Polyene Antifungal Amphotericin Bmentioning
confidence: 99%
“…Most recent evidence in favor of the barrel-stave model was provided by the Murata group, who employed a set of 19 F-and 13 C-labeled AmB derivatives to structurally characterize the AmB-ergosterol channel assembly by solidstate NMR and molecular dynamics calculations. [30,31,[39][40][41] Analysis of the assembly of 14-F-AmB using the Centerband-Only Detection of Exchange (CODEX) NMR method to study slow molecular dynamics revealed that an average of seven AmB molecules were present in each assembly. Structural information was gained from crystallographic data and Rotational Echo Double Resonance (REDOR) NMR experiments designed to measure the distance between two selected labeled heteronuclei.…”
Section: Polyene Antifungal Amphotericin Bmentioning
confidence: 99%
“…Recently, some examples have been reported in which interdigitation has a pronounced impact on the association state of membrane-bound molecules such as peptides 26 or drugs. 27 To assess interdigitation, selective measurement of the depth-dependent chain ordering of the bilayer would be a promising approach. TCTEA could also be introduced into lysosphingomyelin to serve as a lipid-mimicking fluorescent probe similar in structure to the VLCFA-bearing SM.…”
Section: Cluster Synlettmentioning
confidence: 99%